2020
DOI: 10.21037/tcr-20-1342
|View full text |Cite
|
Sign up to set email alerts
|

TNFRSF12A and a new prognostic model identified from methylation combined with expression profiles to predict overall survival in hepatocellular carcinoma

Abstract: Background: It has been proved that DNA methylation, as an epigenetic regulatory mode, plays a crucial role in the initiation, progression and invasion of hepatocellular carcinoma (HCC). However, there still are some pathways and factors that regulates the carcinogenesis of HCC remains unclear.Methods: The original datasets comparing DNA methylation, clinical information and transcriptome profiling between HCC and normal controls were downloaded from The Cancer Genome Atlas (TCGA) database. R software was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In other studies, the preferential expression of the gamma-globin genes was regulated by NFE4, which is an indispensable component in the prognostic model of clear cell renal cell carcinoma [29,30]. LINC00989 was con rmed to be associated with the OS prognosis of patients with breast cancer and hepatocellular carcinoma [31,32]. These ndings suggest that cuproptosis might play biological roles in solid tumors other than AML.…”
Section: Discussionmentioning
confidence: 69%
“…In other studies, the preferential expression of the gamma-globin genes was regulated by NFE4, which is an indispensable component in the prognostic model of clear cell renal cell carcinoma [29,30]. LINC00989 was con rmed to be associated with the OS prognosis of patients with breast cancer and hepatocellular carcinoma [31,32]. These ndings suggest that cuproptosis might play biological roles in solid tumors other than AML.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the preferential expression of the gamma-globin genes was regulated by NFE4, which was an indispensable component in the prognostic model of clear-cell renal-cell carcinoma [39,40]. LINC00989 was confirmed to be associated with the OS prognosis of patients with breast cancer and hepatocellular carcinoma [41,42]. These findings suggest that these lncRNAs play biological roles in the pathogenesis of solid tumors, but their functional role in AML needs further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…[33] TNFRSF12A is the smallest of TNF superfamily individuals, contains a short cytoplasmic death domain structure. [34] TNFRSF12A participation to stimulate multiple signal transduction pathways, including nuclear factor kB pathway and predominate in increasing angiogenesis. Studies have shown that QPCT, SCEL and TNFRSF12A have diagnostic value in papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%